Social and Cultural Reality of the Practice of Female Football in the City of Tunja - Vargas-Peña, Maria Camila (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The history of women in the world and their participation in many social spheres such as politics, religion, economics, among others, has been marked by paradigms that have been instituted and legitimized from masculine positions. However, there is one ambit in particular where women have had to make their way with great difficulty, and it is the sports field, particularly regarding their participation in sports that are traditionally played by men, such as football. In Colombia, a country characterized by the reaffirmation of patriarchal thinking, recognizing the quality of women's football has been very difficult, and even more so since this industry is marked by the existence of a gender gap with a tendency to underestimate women, as well as discriminate and ignore them as  professionals. Within this industry, women continue to play an unequal social role, where their possibilities of giving their opinion, leading or emerging are limited, often being subjected to unfair treatment. Added to this, the perception that society has of female players causes them to be singled out and judged, rather than their triumphs and achievements being highlighted. This is why it is necessary to make this situation visible and invite the community and the school to reflect on this problem, with the aim of transforming gender imaginaries from childhood, allowing girls and women to have the freedom to decide and take part of all social settings without discrimination.